Gestalt Therapy and the Counsellor - Peavy, R. Vance (Canadian Journal of Counselling and Psychotherapy, 2012)
The article briefly describes the principal values in Gestait Therapy and outlines some of the practices commonly employed in Gestalt work. The development of Gestalt work is briefly described and implications for counsellors are suggested — both as a mode of counsellor training and as an approach to be used by counsellors.